AN ANALYSIS OF SUGARCANE AND SUGAR SUPPLY CHAIN IN UTTARADIT PROVINCE A CASE STUDY: THAI IDENTITY SUGAR FACTORY CO., LTD - Khanongnuch, Thanida; Muangwai, Alongkorn; Tantiwattanodom, Channarong (วารสารวิชาการเทคโนโลยีอุตสาหกรรมและวิศวกรรม มหาวิทยาลัยราชภัฏพิบูลสงคราม, 2023)
This research aimed to analyze sugar cane and sugar supply chains in Uttaradit Province, a case study of Thai Identity Sugar Co., Ltd. It started with farmers processing sugarcane into various products and studied problems and obstacles in the supply chain system. It also presented a solution and development of sugarcane and sugar supply chains in Uttaradit Province. The study was divided using the value chain into primary and support activities. Besides, the analysis tools for quality management were the cause-and-effect diagram and SWOT analysis that helped to assess the potential of sugar cane and sugar supply chains in Uttaradit Province. The above research results were known to the sugar production process from the beginning to the end products. It would help increase efficiency. Moreover, it was finding ways to improve the sugarcane and sugar supply chains of Uttaradit Province. It was helpful for sugarcane farmers to know the basics to improve and continuously increase efficiency within the cane and sugar supply chain in the future. It also increased the ability to compete in the market as well.